Supramolecular assembly of pentamidine and polymeric cyclodextrin bimetallic core–shell nanoarchitectures - Hada, Alexandru-Milentie; Burduja, Nina; Abbate, Marco; Stagno, Claudio; Caljon, Guy; Maes, Louis; Micale, Nicola; Cordaro, Massimiliano; Scala, Angela; Mazzaglia, Antonino; Piperno, Anna (Beilstein Journal of Nanotechnology, 2022)
Advanced nanoscale antimicrobials, originated from the combination of noble metal nanoparticles (NPs) with conventional antimicrobial drugs, are considered the next generation of antimicrobial agents. Therefore, there is an increasing demand for rapid, eco-friendly, and relatively inexpensive synthetic approaches for the preparation of nontoxic metallic nanostructures endowed with unique physicochemical properties. Recently, we have proposed a straightforward synthetic strategy that exploits the properties of polymeric β-cyclodextrin (PolyCD) to act as both the reducing and stabilizing agent to produce monodispersed and stable gold-based NPs either as monometallic (nanoG) structures or core–shell bimetallic (nanoGS) architectures with an external silver layer. Here, we describe the preparation of a supramolecular assembly between nanoGS and pentamidine, an antileishmanial drug endowed with a wide range of therapeutic properties (i.e., antimicrobial, anti-inflammatory, and anticancer). The physicochemical characterization of the supramolecular assembly (nanoGSP) in terms of size and colloidal stability was investigated by complementary spectroscopic techniques, such as UV–vis, ζ-potential, and dynamic light scattering (DLS). Furthermore, the role of PolyCD during the reduction/stabilization of metal NPs was investigated for the first time by NMR spectroscopy.
Keywords: antimicrobial agents; bimetallic nanoparticles; gold/silver core–shell; Leishmania; pentamidine; polycyclodextrin

(untitled) - Linko, V.; Zhang, H.; Nonappa; Kostiainen, M. A.; Ikkala, O. (Acc. Chem. Res., 2022)

(untitled) - Scala, A.; Neri, G.; Micale, N.; Cordaro, M.; Piperno, A. (Molecules, 2022)

(untitled) - Pajor-Świerzy, A.; Szczepanowicz, K.; Kamyshny, A.; Magdassi, S. (Adv. Colloid Interface Sci., 2022)

(untitled) - Cui, H.; Shao, Z.-S.; Song, Z.; Wang, Y.-B.; Wang, H.-S. (J. Mater. Chem. C, 2020)

(untitled) - Hada, A.-M.; Craciun, A.-M.; Focsan, M.; Borlan, R.; Soritau, O.; Todea, M.; Astilean, S. (Talanta, 2021)

(untitled) - Blommaerts, N.; Vanrompay, H.; Nuti, S.; Lenaerts, S.; Bals, S.; Verbruggen, S. W. (Small, 2019)

(untitled) - Muzammil, S.; Hayat, S.; Fakhar-e-Alam, M.; Aslam, B.; Siddique, M. H.; Nisar, M. A.; Saqalein, M.; Atif, M.; Sarwar, A.; Khurshid, A.; Amin, N.; Wang, Z. (Front. Biosci., 2018)

(untitled) - Ovais, M.; Nadhman, A.; Khalil, A. T.; Raza, A.; Khuda, F.; Sohail, M. F.; Islam, N. U.; Sarwar, H. S.; Shahnaz, G.; Ahmad, I.; Saravanan, M.; Shinwari, Z. K. (Nanomedicine (London, U. K.), 2017)

(untitled) - Alghrair, Z. K.; Fernig, D. G.; Ebrahimi, B. (Beilstein J. Nanotechnol., 2019)

(untitled) - Chen, L.; Liang, J. (Mater. Sci. Eng., C, 2020)

(untitled) - Hochvaldová, L.; Večeřová, R.; Kolář, M.; Prucek, R.; Kvítek, L.; Lapčík, L.; Panáček, A. (Nanotechnol. Rev., 2022)

(untitled) - Botha, T. L.; Elemike, E. E.; Horn, S.; Onwudiwe, D. C.; Giesy, J. P.; Wepener, V. (Sci. Rep., 2019)

(untitled) - Loza, K.; Heggen, M.; Epple, M. (Adv. Funct. Mater., 2020)

(untitled) - Hada, A.-M.; Potara, M.; Astilean, S.; Cordaro, A.; Neri, G.; Malanga, M.; Nostro, A.; Mazzaglia, A.; Scala, A.; Piperno, A. (Carbohydr. Polym., 2022)

(untitled) - Jaiswal, S.; Duffy, B.; Jaiswal, A. K.; Stobie, N.; McHale, P. (Int. J. Antimicrob. Agents, 2010)

(untitled) - Andreana, I.; Bincoletto, V.; Milla, P.; Dosio, F.; Stella, B.; Arpicco, S. (Drug Delivery Transl. Res., 2022)

https://www.who.int/data/gho/data/themes/topics/gho-ntd-leishmaniasis

(untitled) - Brindha, J.; Balamurali, M. M.; Chanda, K. (Front. Chem. (Lausanne, Switz.), 2021)

(untitled) - Micale, N.; Piperno, A.; Mahfoudh, N.; Schurigt, U.; Schultheis, M.; Mineo, P. G.; Schirmeister, T.; Scala, A.; Grassi, G. (RSC Adv., 2015)

(untitled) - Kammona, O.; Tsanaktsidou, E. (Int. J. Pharm., 2021)

(untitled) - Scala, A.; Piperno, A.; Micale, N.; Mineo, P. G.; Abbadessa, A.; Risoluti, R.; Castelli, G.; Bruno, F.; Vitale, F.; Cascio, A.; Grassi, G. (J. Biomed. Mater. Res., Part B, 2018)

(untitled) - Alti, D.; Rao, M. V.; Rao, D. N.; Maurya, R.; Kalangi, S. K. (ACS Omega, 2020)

(untitled) - Awad, M. A.; Al Olayan, E. M.; Siddiqui, M. I.; Merghani, N. M.; Alsaif, S. S. A.-l.; Aloufi, A. S. (Biomed. Pharmacother., 2021)

(untitled) - Bélteky, P.; Rónavári, A.; Igaz, N.; Szerencsés, B.; Tóth, I. Y.; Pfeiffer, I.; Kiricsi, M.; Kónya, Z. (Int. J. Nanomed., 2019)

(untitled) - Pestov, A.; Nazirov, A.; Modin, E.; Mironenko, A.; Bratskaya, S. (Carbohydr. Polym., 2015)

(untitled) - Kordestani, N.; Rudbari, H. A.; Fateminia, Z.; Caljon, G.; Maes, L.; Mineo, P. G.; Cordaro, A.; Mazzaglia, A.; Scala, A.; Micale, N. (Appl. Organomet. Chem., 2021)

(untitled) - De Paula, E. E. B.; De Sousa, F. B.; Da Silva, J. C. C.; Fernandes, F. R.; Melo, M. N.; Frézard, F.; Grazul, R. M.; Sinisterra, R. D.; Machado, F. C. (Int. J. Pharm., 2012)

(untitled) - Santos Braga, S. (J. Inclusion Phenom. Macrocyclic Chem., 2019)

(untitled) - Ovais, M.; Nadhman, A.; Khalil, A. T.; Raza, A.; Khuda, F.; Sohail, M. F.; Zakiullah; Ul Islam, N.; Sarwar, H. S.; Shahnaz, G.; Ahmad, I.; Saravanan, M.; et al. (Nanomedicine (London, U. K.), 2017)

(untitled) - Panniello, A.; Trapani, M.; Cordaro, M.; Dibenedetto, C. N.; Tommasi, R.; Ingrosso, C.; Fanizza, E.; Grisorio, R.; Collini, E.; Agostiano, A.; Curri, M. L.; Castriciano, M. A.; et al. (Chem. – Eur. J., 2021)

(untitled) - Mowbray, C. E.; Braillard, S.; Speed, W.; Glossop, P. A.; Whitlock, G. A.; Gibson, K. R.; Mills, J. E. J.; Brown, A. D.; Gardner, J. M. F.; Cao, Y.; Hua, W.; Morgans, G. L.; et al. (J. Med. Chem., 2015)